2013
DOI: 10.2478/v10247-012-0097-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of erosion and tillage on the productivity and quality of selected semiarid soils of Iran

Abstract: A b s t r a c t. This greenhouse research was carried out to study the effects of water and tillage erosion on agricultural productivity and soil quality in soil samples from a semiarid region of Iran. A factorial experiment of complete randomized block design was used to compare the effects of soil erosion (eroded and non-eroded soils), slope position, water stress and fertilizer (N-P-K) on yield and yield components of wheat as soil productivity index. The results showed that erosion ie water and tillage ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…In another investigation evaluating the effects of water and tillage erosion on soil quality in semiarid region of Iran, Mehdizade et al . () found that both water and tillage erosion impacted negatively on soil organic matter, N and K contents, and hydraulic conductivity. Meydani et al .…”
Section: Introductionmentioning
confidence: 99%
“…In another investigation evaluating the effects of water and tillage erosion on soil quality in semiarid region of Iran, Mehdizade et al . () found that both water and tillage erosion impacted negatively on soil organic matter, N and K contents, and hydraulic conductivity. Meydani et al .…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural practices, in particular tillage and traffic of machinery, add an extra variation, affecting the movement of water and nutrients, the carbon and nitrogen balance, and the root growth of plants (Strudley et al 2008). These effects drive the development of alternative tillage systems, like no tillage, with the purpose of decreasing the negative impacts of plowing such as carbon losses or erosion (Haring et al 2013;Mehdizade et al 2013;Seitz et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Uma das alterações que ocorre é a formação de encrostamento superficial, característica comum de solos cultivados em várias regiões do mundo (KINNELL, 2005;HU et al, 2012;DALLA ROSA et al, 2013). A formação de crostas superficiais no solo tem consequências diretas para o desenvolvimento das culturas e para a qualidade ambiental, pois reduz a infiltração de água no solo e a disponibilidade de água para as raízes das plantas, dificulta a emergência de plântulas devido à compactação da camada superficial do solo, aumenta o escoamento superficial e a erosão hídrica (ASSOULINE, 2004), reduz a produção agrícola e provoca impactos ambientais, como a contaminação de solo e da água através do transporte de insumos agrícolas, e o assoreamento de cursos d'água e reservatórios pela deposição de partículas do solo oriundas do destacamento e transporte pela ação do fluxo de água (TOUMA et al, 2011;VAEZI;BAHRAMI, 2014;MONTANARELLA et al, 2016).…”
Section: Introductionunclassified